Early pregnancy exposure to benzotriazoles and benzothiazoles in relation to gestational diabetes mellitus: A prospective cohort study. (February 2020) - Zhou, Yanqiu; Qu, Jingyu; Liu, Wenyu; Liao, Jiaqiang; Li, Ying; Zhao, Hongzhi; Li, Jiufeng; Jin, Hangbiao; Liu, Hongxiu; Fang, Jing; Sun, Xiaojie; Jiang, Yangqian; et al.
Highlights: The associations of urinary BTs with the blood glucose levels were investigated. Urinary levels of 2-OH-BTH were positively associated with 2-hour blood glucose. Higher urinary levels of 2-OH-BTH were associated with increased risk of GDM. Abstract: Background: Benzotriazoles (BTRs) and benzothiazoles (BTHs) are emerging contaminants with potential insulin modulation activities. Pregnancy exposure to BTs (BTRs and BTHs) may be a risk factor for the development of gestational diabetes mellitus (GDM). However, epidemiological studies are limited. Objectives: We prospectively investigated the associations of exposure to BTs at early pregnancy with the blood glucose levels and the risks of GDM. Methods: A prospective cohort of 1770 pregnant women who were free of diabetes at baseline was established between 2013 and 2015 in Wuhan, China. Urine samples collected at 13.1 ± 1.1 weeks of gestation were analyzed to estimate the exposure level of BTs. The diagnosis of GDM was based on a 75 g oral glucose tolerance test (OGTT) conducted at 26.4 ± 2.4 weeks of gestation. We examined the associations between urinary concentration of BTs and blood glucose levels by linear regression models. The associations of urinary BTs concentrations with the relative risk (RR) of GDM were evaluated by generalized estimating equations with Poisson regression. Effect modifications by fetus sex and pre-pregnancy body mass index (BMI) were further evaluated in the sensitivity analysis. Results: A total of 147 (8.31%) pregnant women were diagnosed with GDM. Median concentrations of urinary BTs did not differ significantly between pregnant women with and without GDM. It was found that urinary levels of benzothiazole and 2-hydroxy-benzothiazole (2-OH-BTH) were positively associated with 2-hour blood glucose ( p for trend < 0.050). Comparing the high exposure group with the low exposure group of 2-OH-BTH, the adjusted RR of GDM was 1.79 (95% CI = 1.18 to 2.69, p for trend = 0.012). Sensitivity analysis indicated that the positive association of the urinary 2-OH-BTH level with the RR of GDM remained significant among pregnant women who had a male fetus (RR = 1.76, 95% CI = 1.02 to 3.03, p for trend = 0.041) and those with a normal pre-pregnancy BMI (RR = 1.85, 95% CI = 1.09 to 3.11, p for trend = 0.034). Conclusions: These findings suggested that higher urinary level of 2-OH-BTH in early pregnancy was associated with impaired glucose homeostasis and the increased risk of GDM. The results underscore the need of follow-up studies to validate the findings and elucidate the underlying biological mechanism.